Persepsi Guru tentang Manajemen Kepala Sekolah dan Disiplin Siswa: Studi Potong Lintang Historis di SMA Negeri 6 Pekanbaru - Tuti Syafrianti; Nabila Firza; Syarifah Nazhirah; Muhammad Syarif Thoyib; Julia Saraswati; Hidayatunnisa Hidayatunnisa (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
This study investigated the relationship between teachers’ perceptions of principal management and their perceptions of student discipline at SMA Negeri 6 Pekanbaru. A quantitative cross-sectional survey design was employed using historical data collected from March to April 2012. The study population comprised 70 teachers, of whom 60 were selected using the Taro Yamane formula. Data were collected through five-point Likert-scale questionnaires measuring four principal management functions planning, organizing, directing, and controlling and student discipline indicators, including punctuality, attendance, compliance with school regulations, neatness, and learning behavior. The data were analyzed using descriptive statistics and simple linear regression. The findings revealed a positive and statistically significant association between teachers’ perceptions of principal management and student discipline, with a regression coefficient of 1.580, t(58) = 15.092, p < .001. The model explained approximately 79.7% of the variance in perceived student discipline (R² = .797; adjusted R² = .794), indicating a strong association within the analyzed sample. Nevertheless, the findings should not be interpreted causally because both variables were assessed through the same respondent group, the study employed a cross-sectional design, potential confounding variables were not controlled, and the data represent a historical school context. The study concludes that effective planning, coordination, implementation, and monitoring of discipline programs are closely associated with teachers’ positive evaluations of student discipline. These findings imply that school leaders should strengthen collaborative, consistent, transparent, educational, and student-supportive discipline management while integrating teacher perceptions with objective disciplinary records and multi-informant evidence.